Long-term stability of clinically relevant chemistry analytes in pleural and peritoneal fluid - Milevoj Kopčinović, Lara (Array, 2020)
Introduction: Our aim was to investigate the stability of clinically relevant analytes in pleural and peritoneal fluids stored in variable time periods and variable storage temperatures prior to analysis. Materials and methods: Baseline total proteins (TP), albumin (ALB), lactate dehydrogenase (LD), cholesterol (CHOL), triglycerides (TRIG), creatinine (CREA), urea, glucose and amylase (AMY) were measured using standard methods in residual samples from 29 pleural and 12 peritoneal fluids referred to our laboratory. Aliquots were stored for 6 hours at room temperature (RT); 3, 7, 14 and 30 days at - 20°C. At the end of each storage period, all analytes were re-measured. Deviations were calculated and compared to stability limits (SL). Results: Pleural fluid TP and CHOL did not differ in the observed storage periods (P = 0.265 and P = 0.170, respectively). Statistically significant differences were found for ALB, LD, TRIG, CREA, urea, glucose and AMY. Peritoneal fluid TP, ALB, TRIG, urea and AMY were not statistically different after storage, contrary to LD, CHOL, CREA and glucose. Deviations for TP, ALB, CHOL, TRIG, CREA, urea and AMY in all storage periods tested for both serous fluids were within the SL. Deviations exceeding SL were observed for LD and glucose when stored for 3 and 7 days at - 20°C, respectively. Conclusions: TP, ALB, CHOL, TRIG, CREA, urea and AMY are stable in serous samples stored up to 6 hours at RT and/or 30 days at - 20°C. Glucose is stable up to 6 hours at RT and 3 days at - 20°C. The stability of LD in is limited to 6 hours at RT.